Association of Fusobacterium nucleatum infection with the clinicopathological characteristics in colorectal cancer patients - Pang, Siew Wai *; Subasri, Armon; Chook, Jack Bee *; Chew, Jactty *; Peh, Kaik-Boo; Lim, Wendy Wan Dee; Peh, Suat Cheng *; Teow, Sin Yeang (Springer, 2024)
Background: Colorectal cancer (CRC) is a global health problem. The gut microbiome is now recognized as an important underlying factor to the initiation and progression of CRC. Fusobacterium nucleatum (FN) is one of the most studied bacteria in the aetiology of CRC. This study provided cohort evidence on the association of FN infection with clinicopathologic features in CRC patients.